Strengthening Mathematical Literacy And Character Development Of Elementary School Students Through A VisiDi-MiPAI Media Based School Digital Corner - Havizul, Havizul (STKIP Singkawang, 2025)
This study aims to strengthen mathematical literacy and student character at SDN 24 Sui Kakap, Kubu Raya Regency, through the implementation of the Pojok Digital Sekolah (Digital School Corner) based on the VisIDi-MiPAI media. The study is motivated by the importance of enhancing students' literacy and character, as well as initial observations showing that some students at SDN 24 Sui Kakap exhibit low levels of basic mathematical literacy (such as calculation skills, time reading, and mastery of multiplication/division). Additionally, several teachers reported encountering character-related issues among students, including lack of discipline, bullying, and disrespectful behavior. This research-based community service project uses a Service Learning approach, consisting of four phases: needs identification, planning, development, and evaluation. Descriptive analysis results indicate a strong tendency among experts to agree that the Digital School Corner has a high impact, based on the median and mode of individual and total scores. Inferential testing using the one-sample Wilcoxon Signed-Rank Test showed statistically significant results (p-value < 0.05), indicating expert consensus that the Digital School Corner has a high to very high impact in strengthening students' mathematical literacy and character.Moreover, focus group discussions (FGD) revealed the need for technical improvements in the VisIDi-MiPAI media, such as slowing down the text display for better readability and adding video and image content. In conclusion, the Digital School Corner has proven to be effective and significantly impactful in supporting educational goals.Penguatan Literasi Matematika Dan Karakter Peserta Didik Sekolah Dasar Melalui Pojok Digital Sekolah Berbasis Media Visidi-MiPAIABSTRAKPenelitian ini bertujuan untuk menguatkan literasi matematika dan karakter peserta didik di SDN 24 Sui Kakap, Kabupaten Kubu Raya, melalui implementasi Pojok Digital Sekolah berbasis media VisIDi-MiPAI. Dilatarbelakangi oleh pentingnya memperkuat literasi dan karakter peserta didik, serta observasi awal yang telah dilakukan menunjukkan sebagian peserta didik di SDN 24 Sui. Kakap mengalami rendahnya literasi matematika dasar (seperti kemampuan berhitung, membaca waktu, dan penguasaan perkalian/pembagian), disamping itu beberapa guru juga menghadapi peserta didik dengan permasalahan karakter seperti kurang disiplin, perundungan, dan sikap tidak hormat. Kegiatan ini merupakan pengabdian berbasis riset dengan pendekatan Service Learning, meliputi empat tahap: identifikasi kebutuhan, perencanaan, pengembangan, dan evaluasi. Hasil analisis deskriptif menunjukkan kecenderungan pendapat para ahli bahwa Pojok Digital Sekolah memiliki pengaruh tinggi, berdasarkan nilai median dan modus dari skor individu maupun total keseluruhan. Uji inferensial menggunakan Wilcoxon Signed-Rank Test satu sampel menunjukkan hasil yang signifikan secara statistik (p-value < 0,05), mengindikasikan bahwa para ahli sepakat jika Pojok Digital Sekolah berpengaruh tinggi hingga sangat tinggi dalam menguatkan literasi matematika dan karakter peserta didik. Selain itu, diskusi kelompok terarah (FGD) mengungkap perlunya perbaikan teknis pada media VisIDi-MiPAI, seperti memperlambat tampilan teks agar lebih mudah dibaca oleh siswa, serta penambahan konten video dan gambar. Kesimpulannya, Pojok Digital Sekolah terbukti efektif dan berdampak signifikan dalam mendukung tujuan pendidikan.Kata Kunci : Literasi Matematika; Penguatan Karakter; Pojok Digital Sekolah; Media Visual Digital Interaktif; Wilcoxon Signed Rank Test Satu Sampel